Non-dispersive infra-red (NDIR) measurement of carbon dioxide at 4.2μm in a compact and optically efficient sensor - Hodgkinson, Jane; Smith, Richard; Ho, Wah On; Saffell, John R.; Tatam, Ralph P. (Elsevier Science B.V., Amsterdam., 2013)
Non-dispersive infra-red (NDIR) gas detection has enjoyed widespread uptake as a result of development of devices in the standard miniature format for gas sensors, consisting of a cylinder with external dimensions of 20mm diameter x 16.5mm height. We present a new design for such a sensor, making use of low-cost injection moulding technology. The design pays particular attention to the problem of maintaining a high optical throughput while providing an acceptable optical pathlength for gas detection. A detailed analysis of the design is presented, with the results of optical raytracing, showing a raytrace estimate for 4% of the total emitted radiation reaching each of two separated detector elements and a pathlength of 32mm. Finally, we show experimental results obtained with as-manufactured devices, with a short-term limit of detection for carbon dioxide (CO2) estimated at 1ppm or a noise equivalent absorption (NEA) of 3x10-5AU.